Chronotype, sport participation, and positive personality-trait-like individual differences. (August 2015) - Laborde, Sylvain; Guillén, Félix; Dosseville, Fabrice; Allen, Mark S
<x xml:space="preserve">Abstract</x> Chronotype and sport participation have been found to relate to positive personality-trait-like individual differences (PTLID). To date, research has focused exclusively on the morningness–eveningness dimension of chronotype, and little is known about the relationship between chronotype and various characteristics of sport participation (e.g. training time). This investigation had three primary objectives: (1) to extend the current evidence base by exploring how sport participation and PTLID relate to chronotype amplitude, (2) to explore how chronotype (morningness–eveningness and amplitude) relates to various characteristics of sport training and competition, and (3) to explore the independent and interrelated contribution of sport participation and chronotype to PTLID. The sample included 976 non-athletes (493 women and 483 men) and 974 athletes (478 women and 496 men). Participants completed a battery of questionnaires targeting sport participation characteristics, six positive PTLID (hope, optimism, perseverance, resilience, self-efficacy and trait emotional intelligence) and chronotype dimensions. Results showed that morningness–eveningness was negatively related to positive PTLID but was unrelated to sport participation. Greater diurnal fluctuations (amplitude dimension) were associated with lower positive PTLID values, lower sport participation, and shorter training durations. Positive PTLID were also associated with better sleep quality and a shorter sleep duration. Chronotype (morningness–eveningness and amplitude) and sport participation had independent associations with PTLID. These findings suggest that changes in sport participation and activity times might be a useful approach to developing positive PTLID.